1998
DOI: 10.1182/blood.v92.3.784
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Relapse by Prospective Reverse Transcriptase-Polymerase Chain Reaction Analysis of the PML/RARα Fusion Gene in Patients With Acute Promyelocytic Leukemia Enrolled in the GIMEMA-AIEOP Multicenter “AIDA” Trial

Abstract: Although the majority of patients with acute promyelocytic leukemia (APL) are potentially cured by treatments combining all-trans retinoic acid (ATRA) and chemotherapy (CHT), a sizable proportion (around 30%) will relapse during follow-up. Retrospective molecular monitoring studies using reverse transcriptase-polymerase chain reaction (RT-PCR) for the specific PML/RARα fusion gene, have shown that a positive test usually precedes the occurrence of hematologic relapse. Prospective RT-PCR analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(85 citation statements)
references
References 18 publications
1
80
0
4
Order By: Relevance
“…As a target for MRD, the ready detection of PML-RARA transcript at the post-consolidation phase by modern PCR-based techniques could improve outcome prediction through the rapid accurate assessment of the response to treatment [143,144]. Several retrospective studies have pointed out that molecular relapse is an independent prognostic factor which precedes the reappearance of APL blasts [84,[145][146][147][148][149][150]. Successive studies established that negative longitudinal PCR assays performed on bone marrow after completing therapy are strongly related with long-term remission.…”
Section: Standardized Molecular Approaches To Study Minimal Residual mentioning
confidence: 99%
“…As a target for MRD, the ready detection of PML-RARA transcript at the post-consolidation phase by modern PCR-based techniques could improve outcome prediction through the rapid accurate assessment of the response to treatment [143,144]. Several retrospective studies have pointed out that molecular relapse is an independent prognostic factor which precedes the reappearance of APL blasts [84,[145][146][147][148][149][150]. Successive studies established that negative longitudinal PCR assays performed on bone marrow after completing therapy are strongly related with long-term remission.…”
Section: Standardized Molecular Approaches To Study Minimal Residual mentioning
confidence: 99%
“…For patients with PML – RARA ‐positive APL, a key goal is achievement of PCR negativity in the bone marrow using assays that detect one leukaemic cell in 10 4 cells. Patients with persistent disease or molecular relapse, confirmed in two consecutive assays after completion of consolidation, will invariably relapse unless additional therapy is given (Diverio et al , 1998). The optimal management for such patients is uncertain although a matched donor stem cell transplantation (SCT) can be curative (Lo Coco et al , 2003).…”
Section: Acute Promyelocytic Leukaemiamentioning
confidence: 99%
“…The importance of monitoring MRD has been demonstrated in other haematological malignancies, such as acute prolymphocytic leukaemia (APL) and chronic myeloid leukaemia (CML). In patients with APL, the presence of MRD is highly predictive of definite haematological relapse (Diverio et al, 1998). Both prospective and historical comparison studies have shown that patients re-treated at the time of overt haematological relapse have poor survival outcomes compared with patients who are re-treated at the time of molecular relapse (Lo Coco et al, 1999;Breccia et al, 2004).…”
Section: Relevance Of Mrd Eradication In Cllmentioning
confidence: 99%